Highly dispersed polydopamine-modified Mo2C/MoO2 nanoparticles as anode electrocatalyst for microbial fuel cells. (1st September 2018) - Zeng, Lizhen; Chen, Xiaofen; Li, Hongying; Xiong, Juan; Hu, Meihua; Li, Xin; Li, Weishan
Abstract: A novel composite, polydopamine-modified Mo2 C/MoO2 nanoparticles (HD-Mo2 C/MoO2 ), as anode electrocatalyst for microbial fuel cells (MFCs), is synthesized via carbon thermal reduction and following in situ polydopamine modification. The physical and electrochemical characterizations show that Mo2 C/MoO2 nanoparticles can be well dispersed through polydopamine modification and the resulting HD-Mo2 C/MoO2 exhibits excellent electrocatalytic activity compared with unmodified Mo2 C/MoO2 . The MFC using HD-Mo2 C/MoO2 as anode electrocatalyst achieves a maximum output power density of 1.64 ± 0.09 W m −2, which is 39% higher than that using Mo2 C/MoO2 (1.18 ± 0.08 W m −2 ) as anode electrocatalyst. This excellent performance is attributed to modification of PDA, HD-Mo2 C/MoO2 shows better hydrophilicity and electrocatalytic activity toward the direct oxidation of bacterial metabolites than unmodified Mo2 C/MoO2 . Graphical abstract: Image 1 Highlights: HD-Mo2 C/MoO2 is synthesized via carbon thermal reduction and in situ polymerization of dopamine. Polydopamine not only suppresses the aggregation of Mo2 C/MoO2 but also improves hydrophilicity. HD-Mo2 C/MoO2 exhibits excellent catalytic activity toward oxidation of bacterial metabolites.